2010
DOI: 10.1007/s00432-010-0886-8
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of high-risk human papillomavirus (HPV) but not of p53 polymorphisms with oral squamous cell carcinomas in Malaysia

Abstract: This study indicates that high-risk HPV infection is one of the contributing factors for OSCCs. HPV 16 was the predominant type found in Malaysian patients with OSCC. Further, we did not find any association between p53 codon 72 polymorphism and HPV infection or between the p53 polymorphism and the risk of oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
1
27
0
1
Order By: Relevance
“…When comparison was made for all other cancers from India, proline allele was at risk for colorectal cancer and bladder cancer but it was found to be protective in breast cancer and prostate cancer and no association was observed for head and neck cancer (Pandith et al, 2010;Sameer et al, 2010;Suresh et al, 2010;Mittal et al, 2011). Studies from other populations showed conflicting results for the association of Arg72Pro polymorphism with oral cancer risk (Kietthubthew et al, 2003;Kuroda et al, 2007;Saini et al, 2011). Francisco et al (2011) suggested that ethnicity, allelic frequency, histological and anatomical sites may modulate the penetrance of Arg72Pro in cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…When comparison was made for all other cancers from India, proline allele was at risk for colorectal cancer and bladder cancer but it was found to be protective in breast cancer and prostate cancer and no association was observed for head and neck cancer (Pandith et al, 2010;Sameer et al, 2010;Suresh et al, 2010;Mittal et al, 2011). Studies from other populations showed conflicting results for the association of Arg72Pro polymorphism with oral cancer risk (Kietthubthew et al, 2003;Kuroda et al, 2007;Saini et al, 2011). Francisco et al (2011) suggested that ethnicity, allelic frequency, histological and anatomical sites may modulate the penetrance of Arg72Pro in cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that in younger patients, HNSCC arises regardless of the classical risk factors (4)(5)(6)(7)(8)10). HPV infection has been suggested as a possible etiologic factor for such cases (11)(12)(13)(14)(15)(16). HPV was detected in a variety of HNSCCs (11)(12)(13)(14)(15)17) and it was suggested to be associated with lesions of potential malignisation in the head and neck (18,19); however, divergent results are found in the literature regarding the role of HPV presence in HNSCC (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhou et al ) investigated HPV-related HNSCC as a subgroup; however, only three studies were included in the previous meta-analysis (Summersgill et al, 2000;Nagpal et al, 2002;Katiyar et al, 2003). Jiang et al (2013) included four relevant studies (Summersgill et al, 2000;Nagpal et al, 2002;Katiyar et al, 2003;Saini et al, 2011), but no subgroup analysis was performed. In contrast to these previous meta-analyses Jiang et al, 2013), the present meta-analysis only focused on HPV-related HNSCC and nine studies were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies involving 1071 HNSCC cases were included in the meta-analysis (Summersgi ll et al, 2000;Nagpal et al, 2002;Katiyar et al, 2003;Cortezzi et al, 2004;Scheckenbach et al, 2004;Perrone et al, 2007;Hoffmann et al, 2009;Saini et al, 2011;. Figure 1 shows the screening process.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation